AGIHAN HUJAN DAN PENGARUHNYA TERHADAP BANJIR RANCANGAN - , Mutia Prasetya Chusni Putri, ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The designed flood hydrograph can be found with certain return period using a unit hydrograph method. It needs the inputs of designed rainfall in the form of rainfall distribution as a time function. Determining the designed rainfall distribution needs data on rainfall duration and hourly distribution pattern, which can be collected by conducting a study on automatic rainfall data. However, if the data required were not available in the observed region, a rainfall distributionbased approach can be applied. The inappropriate determination of rainfall duration and rainfall distribution pattern using the approach can cause either overestimated or underestimated results of designed discharge, which are not expected in each designing process. In the study, the rainfall distribution-based approach and its rainfall duration used Tadashi Tanimoto rainfall distribution model, Alternating Block Method (ABM) and rainfall distribution patterns from other researchers including Edy Sukoso (2004), Ika Tyasning Yudiyanti (2006) and Sobriyah (2003) that can be applied in the observed catchments, i.e. Progo, Bogowonto, Kupang, Pemali and Lusi. The accuracy of rainfall distribution used was seen from the deviation of designed flood obtained from its comparison with the observed designed flood discharge from the frequency analysis. Result of the analysis on all the rainfall distributions and rainfall duration shows that for Progo at Badran the smallest deviation was Tadashi Tanimoto, for Bogowonto at Pungangan it was the rainfall distribution of Bogowonto, for Kupang at Kuripan Kidul it was Ika Tyasning Yudiyanti rainfall distribution in Wuryantoro subcatchment, for Pemali at Bantarkawung it was ABM rainfall distribution, and for Lusi at Tawangharjo it was Ika Tyasning Yudiyanti rainfall distribution in Temon subcatchment. Rainfall distribution indicating the mostly overestimated designed discharge in Progo, Pemali and Kupang was ABM, and that in Lusi was Envelope curve rainfall distribution. Result of the underestimated discharge in Progo catchment was Temon subcatchment rainfall distribution and for Bogowonto, Kupang and Pemali catchments was Alang subcatchment rainfall distribution.